Стан та безпека регіонального страхового ринку Закарпатської області в умовах воєнного стану - Бачо Роберт; Robert Bacho; Bacsó Róbert; Пойда-Носик Ніна; Poyda-Nosyk Nina; Pojda-Noszik Nina (ФОП Кошовий Богдан-Петро Олегович, 2025)
Резюме. У статті аналізується сучасний стан страхового ринку Закарпатської області, зокрема в умовах російсько-української війни. Дослідження акцентує увагу на ключових тенденціях страхового підприємництва, викликаних міграцією населення, релокацією бізнесу та змінами попиту на страхові продукти. Стаття розкриває проблеми, пов’язані зі звітністю страхових компаній у регіоні, структуру страхових премій та виплат, а також рівень конкуренції на ринку. Закарпаття розглядається як стабільний тиловий регіон, де спостерігається зростання страхових премій, особливо за обов'язковими видами страхування, такими як ОСЦПВВНТЗ і «Зелена картка». Однак відзначено скорочення страхових премій у добровільному сегменті, наприклад, туристичного страхування та страхування життя, через воєнні реалії. В статті пропонуються шляхи підвищення ефективності роботи страхових компаній у регіоні, включаючи адаптацію страхових продуктів до нових умов та розширення співпраці з європейськими партнерами. Зроблено висновок щодо необхідності більш комплексної підтримки з боку держави та регіональної влади для забезпечення сталого розвитку страхового підприємництва в Закарпатській області.

Abastract. The article analyzes the current state of the insurance market in the Transcarpathian region, particularly in the context of the Russia-Ukraine war. The study focuses on key trends in the insurance business driven by population migration, business relocation, and changes in demand for insurance products. It highlights challenges related to the reporting practices of insurance companies in the region, the structure of insurance premiums and payouts, as well as the level of market competition. Transcarpathia is identified as a stable rear region experiencing growth in insurance premiums, especially for compulsory types of insurance such as MTPL (Motor Third-Party Liability) and the Green Card. However, a decline in premiums in the voluntary segment, including travel and life insurance, has been noted due to wartime realities. The analysis of the development of the insurance business in the Zakarpattia region has shown that, on the one hand, an insurance market has been formed and is functioning in the region. On the other hand, the state of development of the insurance business can be assessed as unsatisfactory. This situation has arisen because the existing insurance business in the region developed spontaneously, despite having some historical background, without specially designed development programs or support from the state and regional authorities. Population migration, business relocation, and the region's growing role as a humanitarian and logistical hub create opportunities for development but simultaneously require the adaptation of insurance products and services to new conditions. Alongside positive trends, such as the increased market share of certain companies, challenges are also emerging, particularly related to the rising claims ratio, especially for international policies. The article proposes ways to enhance the efficiency of insurance companies in the region, including adapting insurance products to new conditions and expanding cooperation with European partners. The conclusion emphasizes the need for comprehensive support from the state and regional authorities to ensure the sustainable development of the insurance business in Transcarpathia.
The State and Security of Regional Insurance Market in Transcarpathian Region under Martial Law
Редакційна колегія: https://a-economics.com.ua/index.php/home/about/editorialTeam
Зміст: https://a-economics.com.ua/index.php/home/issue/view/6
Keywords: страхове підприємництво; Закарпаття; премії; страхові виплати; рівень виплат; іnsurance business; Transcarpathia; premiums; insurance payouts; claims ratio